DAMPAK PSIKOLOGI MAHASISWA SELAMA PEMBELAJARAN DALAM JARINGAN DENGAN PENERAPAN ALGORITMA DEMPSTER SHAFER - Marlince N. K. Nababan; Krisman Simatupang; Andi Sanjaya Simanjuntak; Deliana Deliana; Cristina Julyani Sinaga (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
The Covid-19 pandemic is major epidemic that is currently being experienced throughout the world. The pandemic has lowered the structure of the economy, social, culture and even the world of education. As a result, Governments around the world issue Distance Education policies so that this has an impact on the lessons learned for students or students. Especially for University Prima Indonesia students who are the scope of research carried out by researchers to determine the psychological impact of students on learning in the covid-19 pandemic network. Psychological impact in question is whether students experience mental changes, changes in way of thinking, emotional changes, social changes or less physically and mentally healthy. With symptoms, namely depression, anxiety, excessive fear, changes in sleep patterns, economic decline, hampered activity. The results of the study obtained a valid percentage level of symptoms worth 0.8%. The method used in analyzing psychological impact of students is dampster shaper. Expert system methods are often used in research because of the recognized analytical results.